Representações sociais de docentes de cursos de graduação em Enfermagem sobre promoção da saúde - Enilmar da Cunha de Carvalho (2009)
This is a study based in the Social Representativeness Theory developed according to the theoretical-methodological reference of the Central Nuclei Theory. The purpose was to analyze the Nursing professors social representativeness on providing health, from Superior Educational Institutions. The research was made with nursing professors from three different graduation courses from Nursing Superior Educational Institutions in the metropolitan area of Belo Horizonte. The sample was of 124 professors out of a universe of 180 from the Institutions mentioned above. Data collection was made under the form of a questionnaire in which they were asked to wright down 5 (five) words or expressions quickly when they were told the term Health Promotion. The analyzes of this material was made using the technique of the table of four houses, created by Pierre Vergès and the software Ensemble de Programmes Permettent lAnalyse (EVOC) version 2003 computed these data after the formation of the analyzes corpus. The material was analyzed by the software which calculated the simple frequency of each evocated word, the average order of each word and the average of the average order of the words, generating the information used by the researcher in the technique of 4 houses. The results show that the permanent relations and the changes of this social group with the health promotion paradigm and its relation with the traditional health model either the fragmented or the complete, plural and vast ones. It was noticed that the health promotion is inserted in the historical and practical evolution of the health job, the public politics and some pedagogical models. It was stated that the prevention and the education represent what was the consensus of the group and its presence in the left superior quadrant of the professors group and its variations. The term prevention was detached. The empirical dimensions constituted by the professors seem to target a closer relation to the biomedical model. For the majority of the professors, the social representativeness are organized around a possible central nucleus with focus is on the healing and the edagogical model perspectives leading to sick healing. This idea, present in the element prevention, reinforced by the terms politics and assistance, is anchored in the presumptive campaign sanitarianism, main model at the beginning of XX century. Health promotion continues aiming illness prevention through information transmission related to hygiene and considered health habits and also under the influence of technical-scientific knowledge. There is another present dimension which refers to the professional scientifical knowledge valorization and is represented by the patterned elements as reinforced education by politics and assistance which seems to be anchored in the private medical-assistance model that priories a specialized, individual and healing assistance in health. However, there are some appointments which shows that the ideal is due also to education, group-approach, care, life-quality, and determiners, that are present as well mainly in some groups as the group of professors who work on subjects due to basic health services. It was shown that although it is slow, there are changes between the relation of health promotion and the amplified health concept.